PENGUATAN KELUARGA MISKIN MELALUI PEGEMBANGAN MODAL SOSIAL - Bambang Rustanto (Sosio Informa, 2007)
Poverty as a social Phenomena related with economy, social, culture and political dimension. Therefore, need all this dimension to handle that matter so that the poor people could release from the poverty circle. The approaching that should be done by strengthening social capital such social groups that create and develop in their environment. Throught this, they could develop all their potencial to release them from the poverty.Key word : poverty, empowernment, social capital.